INTUITIVE UNDERSTANDING OF EARLY ELEMENTARY SCHOOL STUDENTS IN CONSTRUCTING THE AREA - Amir, Mohammad Faizal (Universitas Negeri Malang, 2019)
During this time students failed to understand the broad concept of the area because they did not have an intuitive understanding structured beforehand in early grade elementary school students. The research focuses on the strategies and intuitive development of students in measuring the area in 20 third grade students of elementary school. The research method used is descriptive qualitative. Students are given 3 assignments in different times and selected subjects based on different characteristics that appear each one for interviews. The findings of this research are 2 visual-concrete covering strategies and measurement estimation. As well as 6 levels of development of intuitive understanding namely level 0: incomplete covering, level 1: primitive covering, level 2: visual-concrete covering, level 3: covering array constructed from unit, level 4: covering constructed by measurement estimation, level 5: array Constructed constructed by measurement, level 6: array implied, solution by calculation